Animal species traded as ethnomedicinal resources in the Federal District, central west region of Brazil - Costa-Neto, Eraldo Medeiros (2010)
ABSTRACT: Animals have been used as treatment for various illnesses by many human cultures. This paper explores the phenomenon of zootherapy in the Federal District, Central West region of Brazil. Fieldwork was carried out from September to October 2006 by visiting one permanent free market in each of three cities within Brazilian Federal District. Data were obtained by open-ended interviews of six traders (four women and two men), who were questioned about zootherapeutic species, modes of use and administration of the folk remedies, as well as the diseases for which they are prescribed. A total of 30 animals belonging to nine taxonomic groups were recorded. Fats are the body parts most cited as sources of medicines (n= 21; 57%), but other raw materials including leather, feather, gizzard, cartilage, liver (bile), milk, and spines are used to prepare both traditional medicines and charms. Zootherapy should be viewed from the multidimensional perspective of sustainable development. The exploration of animals for medicinal purposes should be a major subject in discussions on conservation biology, public health policies, sustainable management of natural resources, bioprospection and patents.